Psychopathology and Quality of Life in Traumatized or Victimized Underage Individuals as Factors for Forensic Multilevel Assessment—A Pilot Investigation - Voelkl-Kernstock, Sabine; Kletecka-Pulker, Maria; Felnhofer, Anna; Kothgassner, Oswald David; Skala, Katrin; Hansmann, Brigitte; Wenzel, Thomas (Frontiers in Psychiatry, 2019)
Psychological sequels to criminal violence can be long lasting and severe. In many countries they are not sufficiently considered in court cases as an important to assess the severity of a crime, guide redress, compensation and rehabilitation of the victim, and - in children - child custody considerations. So far, the focus of forensic assessment has often been limited to diagnostic categories, especially “Post Traumatic Stress Disorder”, a diagnosis with at present rapidly changing definitions in and between diagnostic systems. Other indicators such as quality of life might be of equal importance as compared to clinical or research diagnostic categories to understand and evaluate the impact of a crime and redress needs. Symptoms might differ depending based on the crime encountered. Objective and Methods: Quality of life (QoL) and general symptom patterns including PTSD were assessed in a group of 10-17 year old minors with (N=33) and without (N=49) PTSD diagnosis who all had experienced sexual abuse, physical abuse, death of a parent, or their parents’ divorce, using standardized diagnostic instruments. Results: PTSD patients reported a significantly lower QoL than non-PTSD controls. Reported symptom patterns with potential impact on life, such as intrusive thoughts, differed between the victims of different crime types, with the highest rates of both intrusive symptoms and combined symptom profile in victims of sexual abuse. Data indicate that the changes between older and present criteria and between DSM 5 and recently published ICD 11 might help identify different groups and symptom profiles. Conclusion: Specific trauma related symptom profiles integrating not only general diagnostic categories but the type of crime encountered and especially their its individual impact on quality of life may help guide improve future forensic assessment and guide compensation and rehabilitation plans. Attention should be paid to the challenges when comparing results of diagnostic assessment in the new systems of DSM 5 and ICD 11. Carefully designed studies are now needed to further explore the use and forensic usafeasibility of complex indicators and the impact of violence in different forensic settings. These including civil and criminal law cases but also custody and welfare related evaluation.